2019
DOI: 10.4236/jcc.2019.73002
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality Assessment through FSIM, SSIM, MSE and PSNR—A Comparative Study

Abstract: Quality is a very important parameter for all objects and their functionalities. In image-based object recognition, image quality is a prime criterion. For authentic image quality evaluation, ground truth is required. But in practice, it is very difficult to find the ground truth. Usually, image quality is being assessed by full reference metrics, like MSE (Mean Square Error) and PSNR (Peak Signal to Noise Ratio). In contrast to MSE and PSNR, recently, two more full reference metrics SSIM (Structured Similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
347
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 891 publications
(477 citation statements)
references
References 12 publications
2
347
0
7
Order By: Relevance
“…The FSIM measures the similarities between the features of two images. One study [126] showed that SSIM and FSIM provide perception errors based on the human visual system, while PSNR and MSE provide absolute errors. Therefore, the performance metrics SSIM and FSIM are easy to understand for measuring performance, compared to PSNR and MSE.…”
Section: Performance Metrics For Evaluating Watermarking Systemmentioning
confidence: 99%
“…The FSIM measures the similarities between the features of two images. One study [126] showed that SSIM and FSIM provide perception errors based on the human visual system, while PSNR and MSE provide absolute errors. Therefore, the performance metrics SSIM and FSIM are easy to understand for measuring performance, compared to PSNR and MSE.…”
Section: Performance Metrics For Evaluating Watermarking Systemmentioning
confidence: 99%
“…In this paper, the image quality is measured by comparing the PSNR of the images. The structures of the noise reduction image and the original image are compared by calculating the structural similarity index measurement (SSIM) [30] between them. The value range of SSIM is [0, 1].…”
Section: B: Image Enhancement Region Definitionmentioning
confidence: 99%
“…Whereas PSNR uses video signals as objective parameters. PSNR compares the signal from each video frame in the video source with each video output frame and measures the difference between them [20]. The ratio of the two videos/images is computed in decibels.…”
Section: Assessment Parametersmentioning
confidence: 99%